Prognostic implications of renal function trajectories in heart failure management - A.Z. Y., Koh; B. K., Chung; Hwei Sung, Ling; C. Z. F., Chua; W. K., Ho; K. C., Cheah; S. L., Kwa; J., Namasoo; C. H., ChaI; P. W., Ting; M. J., Khaw; J. K. W., Wong; et al. (European Society of Cardiology, 2025)
Introduction: The interaction between the heart and kidneys, known as cardiorenal syndrome, means that worsening renal function (WRF) in heart failure can lead to a vicious cycle, where declining renal function further impairs cardiac performance. Monitoring and managing WRF in heart failure is crucial, as it is associated with poorer prognosis, increased hospitalization rates, and higher mortality.